Phase diagrams of incommensurate ferroelectric NH₄HSeO₄: phenomenological treatment - Kityk, A.V.; Zadorozhna, A.V. (Condensed Matter Physics, 2000)
The phenomenological analysis of the pressure-temperature (P −T ) phase
diagram of NH₄HSeO₄ crystals is presented. It is shown that the disagreement between the experimental results and the theory may be removed
assuming that the coefﬁcient of the Landau free-energy expansion κ at the
gradient term (dq/dz)(dq∗/dz) changes the sign in the experimental range
of pressures. According to the present model the triple point observed in
NH₄HSeO₄ at PK ≈ 455 MPa, TK ≈ 236 K may be considered as artiﬁcial
points which result from the limitation of experimental resolution. Therefore, even above PK there still exist two very close (unresolved) lines of the
incommensurate phase transitions. Представлений феноменологічний аналіз фазової діаграми тисктемпература (P − T ) кристалів NH₄HSeO₄. Показано, що неузгодження між експериментальними результатами і теорією може
бути зняте, припускаючи, що коефіцієнт κ при градієнтному члені
(dq/dz)(dq∗/dz) в розкладi вільної енергії Ландау змінює знак в області
прикладеного тиску. Відповідно до представленої моделі, потрійна
точка, спостережена в NH₄HSeO₄ при PK≈ 455 MPa, TK≈ 236 K, може
розглядатись як штучна точка, яка є результатом експериментального обмеження. Отже, навіть вище PK ще існують дві дуже близькі лінії
неспівмірних фазових переходів.